A Narrative Review: The Multi-Mechanistic Impact of Sedentary Lifestyle on Mental Health and the Targeted Role of Recreational Sport as a Mitigation Strategy - Andi W Fajriansyah AlGhifari (CV Lentera Cendekia Indonesia, 2025)
In an effort to address contemporary public health challenges, this literature review aims to present a synthesis of evidence demonstrating the link between physical inactivity (sedentary lifestyle) and the deterioration of mental health, while simultaneously validating the potential of recreational sport as a sustainable mitigation solution. The trend of sedentary behavior—defined as time spent in a sitting or reclining position—continues to escalate alongside rapid global digitalization. This increasing duration of inactivity consistently shows a significant negative correlation with a decline in the quality of both physical and mental health. This article reviews several studies focusing on outcomes such as depression and anxiety. The synthesis of empirical evidence indicates a significant positive correlation between prolonged sedentary behavior and the increased risk and severity of depression and anxiety symptoms. Conversely, it is found that participation in recreational sport, which is structured, enjoyable, and voluntarily undertaken, can serve as an effective protective strategy. Recreational sport mediates negative impacts through the release of endorphins, improved sleep quality, and increased social interaction. As a primary recommendation, the findings of this review suggest that public health policies must proactively incorporate and prioritize recreational sport as an effective approach for the mitigation and management of mental health issues, given its significant role in enhancing well-being in the digital age.